The use of medicinal plants in the treatment of common dental situations in primary health care (Research, Society and Development, 2022)
The use of plants to treat health problems is something common to all human cultures and Brazil is privileged for having a great biodiversity of plant species. Many plants already have studies that prove their effectiveness for the treatment of very common human diseases and other plants are widely used by the population, but they lack reliable studies that prove their effectiveness. The use of herbal medicine is already regulated in dentistry, however, there are few professionals who use this resource in clinical practice and who prescribe herbal medicines to their patients. The objective of this work is to carry out a literature review and demonstrate through reliable references that it is possible to prescribe the use of medicinal plants for the treatment or assistance in the treatment of the most common dental situations in Primary Health Care (PHC). Plants indicated for use in the treatment of dental caries, periodontal diseases, oral soft tissue injuries and halitosis are presented, indicating for each plant: popular name, part used, form of use, dosage, route of administration, properties and contraindications. This review showed that the use of medicinal plants in dentistry in PHC is feasible, with scientific support, using easily accessible plants, valuing popular knowledge. It is hoped that this work will serve as a basis for the training and continuing education of dental surgeons in the municipal health network, enabling other ways to meet the demands of PHC patients who seek dental services.